2011
DOI: 10.53855/bjt.v14i2.201
|View full text |Cite
|
Sign up to set email alerts
|

Transplante Renal Em Receptor Com Síndrome De Ochoa E Insuficiência Renal Crônica - Relato De Caso

Abstract: Os autores relatam o caso de uma paciente do sexo feminino, 21 anos, com diagnóstico de Síndrome de Ochoa e portadora de Insuficiência Renal Crônica (IRC) dialítica, submetida a transplante renal com doador falecido e sua evolução pós- transplante. O Transplante renal é uma opção segura para pacientes com Síndrome de Ochoa que evoluem para IRC terminal, apesar do risco aumentado de infecção do trato urinário pós-transplante. A ampliação vesical com ou sem derivação urinária externa continente, além do cateteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In a case series of 50 patients with urofacial syndrome between 1965 and 1991 by Ochoa, it was found that 100% of them had sphincter-detrusor dyssynergia and trabeculated bladders, 44% of them had overactive bladders, 30% had uninhibited contractions and 64% a variable degree of vesicoureteral reflux (VUR). As for the findings of lagophthalmos, it is accompanied by persistent ocular symptoms and exposure keratopathy [18]. It can be a clinical characteristic observed by parents, guardians or people who live with it for a long time, but it can also be manifested in such a light way, not being found or found again.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a case series of 50 patients with urofacial syndrome between 1965 and 1991 by Ochoa, it was found that 100% of them had sphincter-detrusor dyssynergia and trabeculated bladders, 44% of them had overactive bladders, 30% had uninhibited contractions and 64% a variable degree of vesicoureteral reflux (VUR). As for the findings of lagophthalmos, it is accompanied by persistent ocular symptoms and exposure keratopathy [18]. It can be a clinical characteristic observed by parents, guardians or people who live with it for a long time, but it can also be manifested in such a light way, not being found or found again.…”
mentioning
confidence: 99%
“…There is a high chance that the patient will progress to terminal CKD, mainly due to late diagnosis, and it is important to note that there are few cases of successful transplants in these patients, as there is an increased risk of post-transplant UTI [18,19]. In less severe situations, bladder enlargement is recommended, either with or without continent external urinary diversion.…”
mentioning
confidence: 99%
See 1 more Smart Citation